The folklore muse: poetry, fiction, and other reflections by folklorists - De Caro, Frank, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2008)
Folklore--the inherently creative expression, transmission, and performance of cultural traditions--has always provided a deep well of material for writers, musicians, and artists of all sorts. Folklorists usually employ descriptive and analytical prose, but they, like scholars in other social sciences, have increasingly sought new, creative and reflexive modes of discourse. Many folklorists are also creative writers, some well known as such, and the folk traditions they research often provide shape and substance to their work. This collection of creative writing grounded in folklore and its study brings together some of the best examples of such writing.--Provided by publisher.
The Folklorist's Endeavor: An Introduction -- Being or Becoming a Folklorist -- Rock and Word / Steve Zeitlin -- Shelfscapes / Daniel Peretti -- Travels / Libby Tucker -- Work Song / Edward Hirsch -- Instructions for Installing Blinds, "Woman, 41 (Motif GYN041)" / Jeannie Banks Thomas -- Barbara, "Julia," "Amanda in the Mornings" / Steve Zeitlin -- 'Affectionados': What My Mother Taught Me about Language / Joanne B. Mulcahy -- Women and Water in Senegal / Mary Magoulick -- In Search of Our Mothers .. and Our Selves / Elaine J. Lawless -- Folk Communities, Informants / Fieldwork -- Oral History / Frank de Caro -- White Blues and Miss Lena / Cynthia Levee -- Margaret, "Cat" / Steve Zeitlin -- Karl and Janie / Jens Lund -- Historical Sign / Ted Olson -- Opening Camp, "Where the Living Keep Watch," "Echo, at Lakeside," "In Jewelweed" / Margaret Yocom -- Second Growth / William Bernard McCarthy -- Percy / Jeff Todd Titon -- from Bigfoot Stole My Husband / Teresa Bergen -- Performance -- Legends, Rumors, Lore, and Revelation (Some Incomplete) Involving Leaton Troutwine, a Local Eccentric/Celebrity/Hero (and Gordon's Owner) / Matt Clark -- The Storytelling Wake / Steve Zeitlin -- Rant, "Ceci," "Painting Louise Glück" / Leslie Prosterman from Kamp: A Memory Novel / John Burrison -- Shins around the Fireside (Jig) / Jeannie Banks Thomas -- Maybelle and Sara on the Porch / William Bernard McCarthy -- The Powers of Narrative -- "Ballad Girls" / Frank de Caro -- "Stella Stories" / Kirin Narayan -- "Once Upon a Time," "Tickling the Corpse," "Mirror" / Steve Zeitlin -- Legend and Myth -- "A Cosmology of Women" / Mary Magoulick -- "Absent Gods" / Carrie Hertz -- "Glaukos," "Shadow" / Paul Jordan-Smith -- "The Ramayana .. as if Sita Mattered" / Danusha Goska -- Material Things / Material Traditions -- "One of My Mothers" / Holly Everett -- "The Quilters" / Steve Zeitlin -- "Grandma Effie and the Heirloom" / Laurel Horton -- "My Great-Great Half-Uncle Horace's Bone-Handled Jackknife" / Jo Radner -- "The Cane" / Margaret Yocom -- Children's Lore and Language -- "my mother's garden," "arrowhead," "shadow-play," "tag," "red rover" / Susan Stewart -- "The Lulu Bird Nestles in the Daddy O Tree," "Folksay," "The Tenderness of Swine" / Steve Zeitlin -- from Lost in Redskirt Forest / Neil R. Grobman -- Ritual and Custom -- "The Birthday Horse" / William Bernard McCarthy -- "In Praise of Bodies," "Hands and Hearts in the Days of the Dead in Oaxaca, Mexico" / Rosan Augusta Jordan -- "Christmas Tree" / Ted Olson -- "Madhulika" / Steve Zeitlin -- "Eating Alone" / Margaret Yocom -- from Cabañuelas: A Love Story / Norma E. Cantú -- Worldview and Belief -- "Salem, Massachusetts, Playground at Gallows Hill" / Jeannie Banks Thomas -- "Haints" / Teresa Bergen.
Keywords: Folklorists' writings, American; Folklore -- Literary collections; Folklorists -- Literary collections; American literature -- 21st century